Histopathological analysis of unilateral condylar hyperplasia: difficulties in diagnosis and characterization of the disease. Issue 5 (May 2016) - Vásquez, B.; Olate, S.; Cantín, M.; Sandoval, C.; Fariña, R.; del Sol, M.
Abstract: The aim of this study was to perform a histological analysis of the conditions in patients undergoing surgery for unilateral condylar hyperplasia (UCH) using different histopathological analytical techniques and to describe the complications and existing controversy in order to better define the disease. A partial condylectomy was performed in five patients who had been diagnosed with UCH using clinical and imaging methods. The samples obtained were analyzed using routine histological techniques including haematoxylin–eosin, Van Gieson, picrosirius, alcian blue/haematoxylin–eosin, and AgNOR staining. The analyses were performed by an observer who was blinded to the clinical parameters of the disease. The cellularity, tissue layers, size of the anatomical structures, and the relationships between them were assessed. The analysis of these patients was complemented by a review of the scientific literature. Variability was observed in the analysis of the cases. The presence of connective tissue was detected at the bone level, with cartilage formation at different levels. Each island presented levels of involvement that could indicate various degrees of aggressiveness. Type I collagen was observed in most cases, although type III was also identified. The development of histological diagnostic methods to determine the aggressiveness or level of involvement in UCH is not currently possible. Further studies are needed to establish new histological classifications.